TRIBOLOGICAL BEHAVIOR OF POLYMERIC MATERIALS FOR HYBRID METALLOPOLYMER UNITS OF DRY SLIDING FRICTION. PART. 3. POLYETH-ERIFERKETONS, TERETHTHALANES - Чернець, Мирон; Корнієнко, Анатолій (Problems of Friction and Wear, 2022)
According to the method of model triboexperimental studies of materials during sliding friction according to the scheme of end friction, the wear resistance of polyester PEEK and its composite PEEK + 30GF, terephthalene ethylene PET and its composite PET + PTFE was determined. They are used in metal-polymer (MP) gears and plain bearings operating in conditions of dry sliding friction. Their wear resistance indicators are established, based on which the characteristics of their wear resistance are determined, as used in the calculation methods of these hybrid tribomechanical systems. Quantitative regularities of tribological behavior of these polymers in tribocouples with steel 45 are established. The results of influence of loading on change of coefficients of sliding friction are resulted.